Ratio of crown-rump distance to total length in preterm and term infants. Issue 4 (August 1986) - Merlob, P; Sivan, Y; Reisner, S H
Abstract : The known measurements for the determination of body proportions cannot be used practically in the neonate. The ratio of crown-rump distance to total length appears the most useful index for objective evaluation of disorders that influence body proportions in the neonate. Normal standards for this ratio in newborn infants from 27 to 41 weeks' gestation are presented in relation to gestational age and birth weight.